Application of Hashing Method in Medical Term Dictionary Application - Irjii Matdoan, Moh. Rahmat; Rasna, Rasna; M Saleh, Sahlan; Sah, Andrian; Lamsir, Seno (International Journal of Engineering, Science and Information Technology, 2024)
The number of words or terms that appear and are used in human life makes it difficult for a person to master all of these words. To overcome this, these words or/terms are compiled in a dictionary, one of which is a dictionary of medical terms. This research aims to create software that can perform its function as a medical terminology dictionary program and implement the Hash method into software that can be used for data search. This research applies the hash method to find the hash value using a rolling hash. The hash method uses input text to be transformed into numbers, thus speeding up the computational process. The application of the hash method in the addressing/storage process in the Database is very efficient in terms of time and place. The output appears in the form of word meaning and hash value. The hash value is raised to know the value of the searched term using the rolling hash formula. With this research, it is hoped that searching for the meaning of medical terms in a computerized manner can be consistent with manual searches.